Clinical and genetic features of UNC13D deficiency with hypogammaglobulinemia - Xiong, Linyan; Zhao, Qin; Zhao, Qian; Zhang, Zhiyong; An, Yunfei; Tang, Xuemei; Kanegane, Hirokazu; Yang, Xi; Zhao, Xiaodong (Frontiers in Immunology, 2025)
BackgroundUNC13D deficiency is the most common form of familial hemophagocytic lymphohistiocytosis (FHL) in Asia. Hypogammaglobulinemia is a rare phenotype observed in both patients with FHL3 and sporadic hemophagocytic lymphohistiocytosis (HLH). Our observations suggest that UNC13D deficiency with hypogammaglobulinemia presents a distinct clinical phenotype compared to other HLH patients. This finding provides valuable clinical insights and may contribute to a more comprehensive understanding of the disease, highlighting the need for further investigation into its genetic and clinical characteristics.MethodsWe retrospectively analyzed the clinical features of five patients with UNC13D deficiency with hypogammaglobulinemia at our center, along with a literature review. The clinical findings were then compared with those of sporadic HLH patients presenting with hypogammaglobulinemia.ResultsAll patients experienced respiratory infections, with two patients showing recurrent episodes. Seizures were observed in 75% of the patients. HLH-related biomarkers were present in all patients. The four patients who did not undergo allogeneic hematopoietic stem cell transplantation (HSCT), all died. Eight variant sites were identified, with 25% located in exon 9 and another 25% in exon 20. The majority (66.67%) of the variants were found in the region responsible for interaction with RAB27α. UNC13D deficiency with hypogammaglobulinemia was associated with a higher frequency of respiratory manifestations, neurological involvement, and an increased mortality rate.ConclusionsOur study presents the first comprehensive description of the clinical features of UNC13D deficiency with hypogammaglobulinemia. Patients with this condition tend to exhibit more severe clinical manifestations and a poorer prognosis. Allogeneic HSCT may help mitigate immune dysregulation.